Synthesis and characterization of new aromatic polyesters containing biphenyl side groups - Honkhambe, Pandurang N.; Avadhani, C. V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2007)
Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50: 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4-isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the polyesters were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidmone. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. WAXD measurements indicated that all the polyesters and copolyesters were amorphous in nature. Glass transition temperature of polyesters were in the range 198-256 degrees C, while the initial degradation temperature of polyesters were in the range 444-481 degrees C. Copolyesters derived from BBHPE exhibited improved solubility and higher glass transition temperatures compared to the corresponding polyesters based on BPA. (c) 2007 Wiley Periodicals, Inc.
Keywords: Aromatic polyesters; biphenyl side groups

Synthesis of aromatic poly(amide-imide)s from novel diimide-diacid (DIDA) containing sulphone and bulky pendant groups by direct polycondensation with various diamines - Patil, Prashant S.; Pal, Ravindra R.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2007)
A novel diimide-diacid (DIDA) monomer, 4-{4-[(4-methyl phenyl) sulphonyl]}-1,3-bis-trimellitoimido benzene containing sulphone and bulky pendant groups was successfully synthesized and used to synthesize a series of wholly aromatic poly(amide-imide)s (PAIs) by direct polycondensation method. The direct polycondensation of newly synthesized DIDA with different diamines was carried Out via Yamazaki's phosphorylation method using triphenyl phosphite and pyridine system. The resulting poly(amide-imide)s were obtained in quantitative yields with inherent viscosities 0.36-0.47 dl/g in DMAc at 30 +/- 0.1 degrees C. The poly(amide-imide)s were amorphous and were readily soluble in various solvents such as N-methyl-2-pyrrolidinone (NMP), NN-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), and pyridine. Tough and flexible films were obtained by casting their DMAc solution. According to thermogravimetric analysis, the polymers were fairly stable up to temperature around 396 degrees C, and 10% weight losses in the temperature range of 476-511 degrees C that showed good thermal stabilities of these polymers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: direct polycondensation; poly(amide-imide)s; sulphone and bulky pendant groups; thermally stable polymers

Synthesis and self-assembling properties of alpha,omega-hydroxy-poly(ethylene oxide) end-capped with 1-isocyanato-3-pentadecylcyclohexane - Kadam, Vijay S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Hourdet, Dominique (Polymer, 2008)
A novel hydrophobic compound, 1-isocyanato-3-pentadecylcyclohexane (PDC) issued from a renewable resource material (Cashew Nut Shell Liquid), is used to end-cap poly(ethylene oxide) (PEO) of different molecular weights. The synthesis, characterization and self-assembling properties of these new associating polymers are reported. In aqueous solution, PDC modified PEOs self-associate into micellar structures which are characterized by neutron scattering. Using a star-polymer model with sticky hard sphere interactions, it is shown that the characteristics of the micelles mainly depend on the size of the PEO chain. In the case of PDC stickers, the aggregation number decreases from 25 to 17 with increasing molecular weight of PEO, from 10 to 20 kg/mol, respectively. The temperature directly impacts the interaction potential between the hydrophilic coronas of PEO which become less repulsive with increasing temperature. Rheological measurements, performed in dilute solution, clearly demonstrate that PEO micelles self-associate into open supramolecular structures. The correlation length of these loose clusters increases with polymer concentration and the hierarchical self-assembly follows the rules of the percolation theory. The sol/gel transition takes place at the overlap concentration of clusters. In semi-dilute solution, the viscoelastic properties of PDC end-capped PEOs are well described by the Maxwell model with a single relaxation mode. The characteristic time of the network follows an Arrhenius temperature dependence with an activation energy of 70 kJ/mol, in very good agreement with the size of PDC stickers. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Hydrophobically end-capped; poly(ethylene oxide); Star micelles

Synthesis and characterization of new polyimides containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Halhalli, Mahadeo R.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
A new unsymmetrical aromatic diamine, viz., 4-pentadecylbenzene-1,3-diamine was synthesized through a series of reaction steps starting from 3-pentadecylphenol. 4-Pentadecylbenzene-1,3-diamine was employed to synthesize a series of new polyimides by one-step polycondensation in m-cresol with four commercially available aromatic dianhydrides. viz., 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone-tetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA). Inherent viscosities of resulting polyimides were in the range 0.33-0.67 dL/g and number average molecular weights were in the range 14,700-52,200 (GPC, polystyrene standard). Polyimides containing pendent pentadecyl chains were soluble in organic solvents such as chloroform, m-cresol, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone (NMP), pyridine and nitrobenzene. Strong and flexible films of polyimides could be cast from their chloroform solutions. Polyimides exhibited glass transition temperature in the range 158-206 degrees C. The temperature at 10% wt. loss (T(10)). determined by TGA in nitrogen atmosphere, of polyimides was in the range 470-480 degrees C indicating good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; Glass transition temperature; Pendant pentadecyl chain; polyimides

Synthesis, characterization and constitutional isomerism study of new aromatic polyamides containing pendant groups based on asymmetrically substituted meta-phenylene diamines - Pal, Ravindra R.; Patil, Prashant S.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
Four new aromatic polyamides containing pendant groups were synthesized by low temperature interfacial polycondensation of two asymmetrically substituted diamine monomers, namely, 4-[4-(1-methyl-1-phenylethyl) phenoxyl-1,3-diamino benzene and 4-[4-[4-methylphenyl) sulphonyl]phenoxy)-1,3-diamino benzene with two aromatic diacid chlorides, namely isophthaloyl chloride and tereplithaloyl chloride. Inherent viscosities of polyamides were in the range 0.64-0.72 dL/g indicating formation of medium molecular weight polymers. The weight average molecular weights and number average molecular weights, determined by gel permeation chromatography (polystyrene standard), were in the range 54,500-65,000 and 19,750-27,000, respectively. The constitutional isomerism of synthesized polyamides was investigated by (1)H and (13)C NMR spectroscopy, where as the constitutional order was calculated from (1)H NMR spectroscopy and was found to be in the range 0.35-0.37. Polyamides containing pendant groups were essentially amorphous and were soluble in polar aprotic solvents such as N, N-dimethyl acetamide, N-methyl-2-pyrrolidone, N, N-dimethyl formamide and dimethyl sulfoxide. Polyamides exhibited glass-transition temperature in the range 237-254 degrees C. The initial decomposition temperature, determined by TGA in nitrogen atmosphere, of polyamides was in the range 371-410 degrees C indicating their good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Asymmetrically substituted diamines; Constitutional isomerism; interfacial polycondensation; Pendant groups

Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship

Synthesis and characterization of polyamides containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
A new aromatic diacid monomer viz., 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid was synthesized starting from cardanol and was characterized by FTIR, (1)H- and (13)C NMR spectroscopy. A series of new aromatic polyamides containing ether linkages and pendant pentadecyl chains was prepared by phosphorylation polycondensation of 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid with five commercially available aromatic diamines viz., 1,4-phenylenediamine, 4,4'-oxydianiline, 4,4'-methylenedianiline, 1,3-phenylenediamine, and 4,4'-(hexafluoroisopropylidene)dianiline. Inherent viscosities of the polyamides were in the range 0.45-0.66 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. The introduction of ether linkages and pendant pentadecyl chains into polyamides led to an enhanced solubility in N,N-dimethylacetamide and 1-methyl-2-pyrrolidinone at room temperature or upon heating. The polyamides could be solution-cast into tough, flexible and transparent films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-Ray diffractograms also displayed a diffuse to sharp reflection in the small-angle region (20 = similar to 2-5 degrees) for the polyamides characteristics of formation of loosely to well-developed layered structure arising from packing of flexible pentadecyl chains. The glass transition temperature observed for the polyamides was in range 139-189 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of the polyamides was in the range 425-453 degrees C indicating their good thermal stability. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkyl side-chain; Cardanol; Cashew nut shell liquid; Pentadecyl chains; polyamides

Synthesis and characterization of polyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4 `-pentadecylphenyl]ethane - More, Arvind S.; Naik, Parimal V.; Kumbhar, Kishor P.; Wadgaonkar, Prakash P. (Polymer International, 2010)
Aromatic polyesters are of considerable interest because of their excellent mechanical properties, chemical resistance and thermal stability. However, most aromatic polyesters are difficult to process due to their high glass transition temperatures coupled with their insolubility in common organic solvents. The present article describes a series of organosoluble polyesters and copolyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane. A series of new aromatic polyesters containing pendant pentadecyl chains was synthesized by interfacial polycondensation of 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC. A series of copolyesters was synthesized from 4,4'-isopropylidenediphenol with TPC by incorporating 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane as a comonomer. Inherent viscosities of the polyesters and copolyesters were in the range 0.72-1.65 dL g(-1) and number-average molecular weights were in the range 18 170-87 220. The polyesters and copolyesters containing pendant pentadecyl chains dissolved readily in organic solvents such as chloroform, dichloromethane, pyridine and m-cresol and could be cast into transparent, flexible and apparently tough films. Wide-angle X-ray diffraction data revealed the amorphous nature of the polyesters and copolyesters. The formation of loosely developed layered structure was observed due to the packing of pendant pentadecyl chains. The temperature at 10% weight loss, determined using thermogravimetric analysis in nitrogen atmosphere, of the polyesters and copolyesters containing pendant pentadecyl chains was in the range 400-460 degrees C. The polyesters and copolyesters exhibited glass transition temperatures in the range 63-82 degrees C and 177-183 degrees C, respectively. (C) 2010 Society of Chemical Industry
Keywords: cashew nutshell liquid; CNSL; pentadecyl; polyesters; renewable

Synthesis and characterization of new organosoluble aromatic polyamides and polyazomethines containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2011)
New aromatic polyamides and polyazomethines containing pendent pentadecyl chains were synthesized by polycondensation of pentadecylbenzene-1,3-diamine with (i) four commercially available aromatic diacids, viz., biphenyl-4,4'dicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid and isophthalic acid, and (ii) dialdehydes, viz., terephthaldehyde, isophthaldehyde and a 50 : 50 mol% mixture of terephthaldehyde, and isophthaldehyde, respectively. Inherent viscosities of polyamides and polyazomethines were in the range 0.35-0.56 dL g(-1) and 0.33-0.38 dL g(-1), respectively, indicating the formation of medium molecular weight polymers. The presence of pendent pentadecyl chains in polyamides and polyazomethines led to an improvement in their solubility in organic solvents. Polyamides could be cast into flexible, transparent and tough films from their solution in N,N-dimethylacetamide while polyazomethines could be solution cast into transparent, flexible and stretchable films from their CHCl(3) solution. (1)H-NMR studies based on amide proton signals and azomethine proton signals indicated the presence of constitutional isomerism in the polyamides and polyazomethines. Wide-angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were amorphous in nature. X-ray diffractograms also displayed sharp reflections in the small angle region (2 theta approximate to 3 degrees) indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition (T(g)) temperatures of polyamides were in the range 169-215 degrees C while T(g) values for polyazomethines were in the range 16-55 degrees C. The temperature for the 10% weight loss of polyamides and polyazomethines were in the range 430-460 degrees C and 425-440 degrees C, respectively, in a nitrogen atmosphere, which indicated their good thermal stability. Polyazomethines were also characterized by UV-Vis and photoluminescence spectroscopy and optical band gap (E(g)) values, calculated according to the maximum of the UV absorption, were found to be in the range 2.82-3.10 eV.
Keywords: High performance polymers; optical band gap; polyamides; polyazomethines; solubility

Synthesis and characterization of organo-soluble poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Honkhambe, Pandurang N.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
Poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant pentadecyl chains were synthesized by polycondensation of each of the two bisphenol monomers viz, 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl] ethane and 1,1-bis(4-hydroxyphenyl)-3-pentadecyl cyclohexane with activated aromatic dihalides namely, 4,4'-difluorobenzophenone, and 1,3-bis(4-fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene, in the presence of anhydrous potassium carbonate. Polymers were isolated as white fibrous materials with inherent viscosities and number average molecular weights in the range 0.70-1.27 dL g(-1) and 76,620-1,36,720, respectively. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were found to be soluble at room temperature in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, and pyridine and could be cast into tough, transparent, and flexible films from their solutions in chloroform. Wide angle X-ray diffraction patterns exhibited a broad halo at around 2 theta = similar to 19 degrees indicating that the polymers containing pentadecyl chains were amorphous in nature. In the small-angle region, diffuse reflections of a typically layered structures resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss, obtained from TG curves, for poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 416-459 degrees C, indicating their good thermal stability. A substantial drop in glass transition temperatures (68-78 degrees C) was observed for poly(ether ether ketone) s and poly(ether ether ketone ketone) s due to ``internal plasticization'' effect of flexible pendant pentadecyl chains. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 3689-3695, 2011
Keywords: alkyl side-chain; Cashew nut shell liquid; CNSL; pentadecyl; poly(arylene ether)s; poly(ether ketone)s; polyethers; renewable

Synthesis of bis-allyloxy functionalized polystyrene and poly (methyl methacrylate) macromonomers using a new ATRP initiator - Sane, Prakash S.; Palaskar, Dnyaneshwar V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2011)
A new bis-allyloxy functionalized ATRP initiator, viz, 4,4-bis (4-(allyloxy) phenyl) penty1-2-bromo-2-methylpropanoate was synthesized starting from commercially available 4,4-bis (4-hydroxyphenyl) pentanoic acid. Atom transfer radical polymerization of styrene in bulk and that of methyl methacrylate in anisole using CuBr/N,N,N',N',N `'-pentamethyldiethyl-enetriamine system was carried out. The kinetic study of styrene polymerization showed controlled polymerization behavior. Bis-allyloxy functionalized well-defined polystyrene (M(n)(GPC): 13,600-28,250, PDI: 1.07-1.09) and poly (methyl methacrylate) (M(n)(GPC): 10,100-18,450, PDI: 1.23-1.34) macromonomers were obtained. The presence of allyloxy functionality was confirmed by (1)H NMR spectroscopy. The reactivity of allyloxy functionality was demonstrated by carrying out organic reactions such as addition of bromine and hydrosilylation on polystyrene macromonomer. Polystyrene macromonomer with bis-allyloxy functionality was transformed into bis-epoxy functionalized polystyrene macromonomer using 3-chloroperoxybenzoic acid. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allyloxy end-functional polymer; Atom transfer radical polymerization (ATRP); Macromonomers; Poly (methyl methacrylate); Polystyrene

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer

Synthesis and characterization of poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant biphenyl and naphthyl groups - Honkhambe, Pandurang N.; Dhamdhere, Neelam A.; Tawade, Bhausaheb V.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
New poly(ether ether ketone)s (PEEKs) and poly(ether ether ketone ketone)s (PEEKKs) containing pendant biphenyl and naphthyl groups were synthesized by nucleophilic substitution reaction of each of the four bisphenols viz., 1-(4- biphenylyl)- 1,1- bis(4- hydroxyphenyl) ethane, 1-(4- biphenylyl)- 1,1- bis(3- methyl, 4- hydroxyphenyl) ethane, 4,4'-[1-(2- naphthalenyl) ethylidene] bis-phenol and 4,4'-[1-(2- naphthalenyl) ethylidene] bis-3-methylphenol with 4,4'- difluorobenzophenone and 1,3- bis(4- fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene in the presence of anhydrous potassium carbonate. Inherent viscosities and number-average molecular weights of polymers were in the range of 0.42-0.86 dl/g and 2.40-7.55 x 10(4), respectively. PEEKs and PEEKKs were amorphous in nature and were readily soluble in a wide range of organic solvents and could be cast into flexible and tough films from chloroform solution. Glass transition temperature of PEEKs and PEEKKs were in the range of 180 degrees C -200 degrees C. T-10 values of PEEKs and PEEKKs were in the range of 424 degrees C-512 degrees C in nitrogen atmosphere, indicating their good thermal stability.
Keywords: biphenyl; bisphenol; naphthyl; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Synthesis and characterization of polyetherimides containing multiple ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Polymer International, 2015)
4-(4-(4-(4-Aminophenoxy)-2-pentadecylphenoxy)phenoxy)aniline (APPPA) was synthesized starting from cashew nut shell liquid-derived bisphenol, i.e. 4-(4-hydroxyphenoxy)-3-pentadecylphenol, by nucleophilic substitution reaction with 4-chloronitrobenzene followed by reduction of the formed 4-(4-nitrophenoxy)-1-(4-(4-nitrophenoxy)phenoxy)-2-pentadecylbenzene. Three new polyetherimides containing multiple ether linkages and pendent pentadecyl chains were synthesized by one-step high-temperature solution polycondensation of APPPA in m-cresol with three aromatic dianhydrides, i.e. 3,3,4,4-oxydiphthalic anhydride, 4,4-(hexafluoroisopropylidene)diphthalic anhydride and 3,3,4,4-biphenyltetracarboxylic dianhydride. Inherent viscosities and number-average molecular weights of the polyetherimides were in the ranges 0.66-0.70 dLg(-1) and 17100-29700gmol(-1) (gel permeation chromatography, polystyrene standards), respectively, indicating the formation of reasonably high molecular weight polymers. The polyetherimides were soluble in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethylsulfoxide, and could be cast into transparent, flexible and tough films from their solutions in chloroform. The polyetherimides exhibited glass transition temperatures (T-g) in the range 113-131 degrees C. The lowering of T-g could be attributed to the combined influence of flexibilizing ether linkages and pentadecyl chains which act as packing-disruptive' groups. The temperature at 10% weight loss (T-10), determined from thermogravimetric analysis in nitrogen atmosphere, was in the range 460-470 degrees C demonstrating good thermal stability. The virtues of solubility and large gap between T-g and T-10 mean that the polyetherimides containing pendent pentadecyl chains have possibilities for both solution as well as melt processability. (c) 2015 Society of Chemical Industry
Keywords: CNSL; ether linkage; pentadecyl; polyetherimide; processability

Synthesis and properties of poly(arylene ether)s based on 3-pentadecyl 4,4'-biphenol - Tawade, Bhausaheb V.; Shaligram, Sayali V.; Valsange, Nitin G.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Polymer International, 2016)
A new biphenol, 3-pentadecyl 4,4-biphenol, was synthesized starting from 3-pentadecylphenol and was polycondensed with 4,4-difluorobenzophenone, 1,3-bis(4-fluorobenzoyl)benzene and bis(4-fluorophenyl)sulfone to obtain poly(arylene ether)s with biphenylene linkages in the backbone and pendent pentadecyl chains. Inherent viscosities and number-average molecular weights (M-n) of the poly(arylene ether)s were in the range 0.50 - 0.81 dL g(-1) and 2.2 x 10(4) - 8.3 x 10(4), respectively. Detailed NMR spectroscopic studies of the poly(arylene ether)s indicated the presence of constitutional isomerism which existed because of the non-symmetrical structure of 3-pentadecyl 4,4-biphenol. The poly(arylene ether)s readily dissolved in common organic solvents such as dichloromethane, chloroform and tetrahydrofuran and could be cast into tough, transparent and flexible films from their chloroform solutions. The poly(arylene ether)s exhibited T-g values in the range 35-60 degrees C which are lower than that of reference poly(arylene ether)s without pentadecyl chains. The 10% decomposition temperatures (T-10) of the poly(arylene ether)s were in the range 410-455 degrees C indicating their good thermal stability. A gas permeation study of poly(ether sulfone) containing pendent pentadecyl chains revealed a moderate increase in permeability for helium, hydrogen and oxygen. However, there was a large increase in permeability for carbon dioxide which could be attributed to the internal plasticization effect of pendent pentadecyl chains. (c) 2016 Society of Chemical Industry
Keywords: cashew nut shell liquid (CNSL); gas permeation study; pentadecyl; poly(arylene ether)s; thermal stability

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.

Sulfamic acid-catalyzed, environmentally benign synthesis of bis-tetronic acids at ambient temperature - Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (Research on Chemical Intermediates, 2017)
An enviro-economic protocol has been described for the synthesis of bis-tetronic acids by pseudo-three-component condensation between aldehydes/isatins and tetronic acid using sulfamic acid as a solid acid catalyst. Easy commercial availability of the catalyst at extremely low cost, excellent yields and avoidance of conventional purification procedures are the main merits of this energy efficient protocol.

Synthesis and characterization of polyhydrazides and poly(1,3,4-oxadiazole)s containing multiple arylene ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Valsange, Nitin G.; Wadgaonkar, Prakash P. (High Performance Polymers, 2017)
A new diacylhydrazide monomer, namely, 4-(4-(4-(4-(hydrazinocarbonyl)phenoxy)-2-pentadecylphenoxy)phenoxy) benzohydrazide (HPPDPB), was synthesized starting from 4-(4-hydroxyphenoxy)-3-pentadecylphenol. HPPDPB was polycondensed with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50:50 mol%) to obtain polyhydrazides containing multiple arylene ether linkages in the backbone and pendent pentadecyl chains. Polyhydrazides were subsequently cyclized in the presence of phosphorus oxychloride to obtain the corresponding poly(1,3,4-oxadiazole)s. Polyhydrazides and poly(1,3,4-oxadiazole)s exhibited inherent viscosities in the range 0.65–0.72 dL g−1 and 0.54–0.62 dL g−1, respectively, which indicated the formation of reasonably high-molecular weight polymers. Polyhydrazides were soluble in polar aprotic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone and pyridine whereas poly(1,3,4-oxadiazole)s exhibited excellent solubility even in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran. Tough, transparent and flexible films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from DMAc and chloroform solutions, respectively. X-Ray diffraction studies revealed amorphous nature of polyhydrazides and poly(1,3,4-oxadiazole)s and the formation of layered structure was observed due to ordered packing of pentadecyl chains. The 10% decomposition temperature (T 10) values for poly(1,3,4-oxadiazole)s were in the range 425–440°C indicating their good thermal stability. Glass transition temperature (T g) values of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 175–192°C and 92–103°C, respectively. The excellent solubility characteristics and the large gap between T g (92–103°C) and T 10 (425–440°C) values give poly(1,3,4-oxadiazole)-containing pendent pentadecyl chains better opportunities for processability.

Spiro [fluorene-9,9 '-xanthene]-containing copolymers of intrinsic microporosity: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2018)
In the present study, a new bis(catechol) containing spiro[fluorene-9,9'-xanthene], namely, 4,4'-(spiro(fluorene9,9'-xanthene]-2',7'-diyl)bis(benzene-1,2-diol) (THSFX) was designed and synthesized. Polycondensation reactions of THSFX and varying compositions of THSFX and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) were carried out with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain a homopolymer and copolymers, respectively. The organo-soluble polymers exhibited reasonably high molecular weights (23300-34,100 g/mol) and could be cast into self-standing films from their chloroform solutions. X-Ray diffraction studies indicated that PIMs were amorphous in nature. These polymers exhibited high thermal stability (T-10 = 490-510 degrees C) and possessed intrinsic microporosity with high BET surface area (360-796 m(2)/g). The gas permeation properties of SFX-PIM-25 and SFX-PIM-33 were evaluated and they exhibited high gas permeability (CO2 = 3595-4034 Barrer). The gas permeability data of SFX-PIM-25 and SFX-PIM-33 was located close to 1991 Robson upper bound for CO2/N-2, CO2/CH4 and O-2/N-2 gas pairs

Synthesis and characterization of partially bio-based polyimides based on biphenylene-containing diisocyanate derived from vanillic acid - Kuhire, Sachin S.; Ichake, Amol B.; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (European Polymer JOurnal, 2018)
A new bio-based biphenylene-containing diisocyanate, namely, 5,5'-diisocyanato-2,2',3,3'-tetramethoxy-1,1'-biphenyl (BDI) was synthesized starting from vanillic acid - a lignin-derived phenolic acid. A series of new partially bio-based polyimides was prepared by polycondensation of BDI with five commercially available aromatic dianhydrides. Polyimides exhibited good solubility in organic solvents and medium molecular weights (Mn (GPC, polystyrene standard) = 25,100-32,200 g mol(-1)). Polyimides showed good thermal stability with 10% degradation temperature and glass transition temperature in the range 459-473 degrees C and 262-329 degrees C, respectively.

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations

Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking

Synthesis, characterization and post-modification of aromatic (Co)polyesters possessing pendant maleimide groups - Jadhav, Uday A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (High Performance Polymers, 2023)
A new series of (co)polyesters possessing pendent maleimide groups was synthesized by low temperature solution polycondensation of 4, 4’-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA) with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of TPC and IPC (50:50 mol %). Copolyesters were also synthesized by polycondensation of varying compositions of BPA-MA and bisphenol-A (BPA) with IPC. The chemical structures and compositions of (co)polyesters were confirmed by NMR spectroscopy. Inherent viscosity values and number-average molecular weights of (co)polyesters were in the range 0.50–0.76 dL/g and 17,700-32,100 g/mol, respectively, indicating the formation of reasonably high molecular weight polymers. (Co)polyesters were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polyesters exhibited 10% weight loss and glass transition temperatures in the range 464–468 and 142–178°C, respectively. A representative copolyester possessing pendant maleimide groups was chemically modified via metal-free azide-maleimide 1,3-dipolar cycloaddition click reaction with two azido compounds, namely, (azidomethyl)benzene (Bz-N3) and 1-(azidomethyl)-pyrene (Py-N3) to yield corresponding modified copolyesters in a quantitative manner.